Nutritional Composition, Toxic ad Antioxidant Properties of Aqueous Extracts of Anacardium Occidentale Linn. Leaves and their Potential Benefits in Atherosclerosis-Induced Rabbits - Fazil, Muhammad Nor Fazali (2011)
Atherosclerosis is the main underlying pathology behind cardiovascular diseases (CVD), which is a major cause of disability and premature death in the world. This present study aimed to investigate the anti-atherosclerotic, hypocholesterolemic, changes in the erythrocyte antioxidant enzymes, hepatoprotective and toxicity effects of the aqueous extract of the leaves of Anacardium occidentale Linn. (AOE) in atherosclerosis-induced rabbits. In vitro antioxidative properties of AOE were assessed via DPPH free radical scavenging and ferric reducing antioxidant power assay (FRAP) while in vitro toxicity potential of AOE was determined via brine shrimp lethality test (BSLT). The total phenolic content of AOE was evaluated via Folin-Ciocalteau method. Atherosclerosis was induced by giving 0.5% high cholesterol diet and AOE of various doses (100, 200 and 400 mg/kg) were administered via force-feeding once daily for 12 weeks. Blood samples were withdrawn via ear vein lobe every 4 weeks. It was demonstrated that AOE was not toxic, contain phenolic compounds and posses comparable antioxidant properties with Buthylated Hydroxytoluene (BHT) in free radical scavenging and FRAP assay. Supplementation of AOE to the experimental animals compared to the rabbits receiving the high cholesteriol diet alone significantly retarded (p<0.05) the atheromatous plaque formation and significantly lower (p<0.05) the low density lipoprotein and triglycerides levels. The extract also posses antioxidative effects in vivo by significantly lower (p<0.05) the lipid peroxidation product (malondialdehyde) and was able to significantly increased (p<005) the catalase levels. The extract also exerts hepatoprotective effect by normalizing the liver enzymes (aspartate transaminase, alkaline phosphatase, alanine transaminase and gamma-glutamyltransferase). In conclusion, this study indicates the potential of AOE as anti-atherosclerotic, hypocholesterolemic and antioxidative agent.